探析中印文化碰撞之跨文化交际——以中国赴印尼汉语教师的工作学习生活采访为例 - Paula Aretha (Sinolingua: Journal of Chinese Studies, 2024)
With the opening and development of Chinese language education in Indone-sia, the number of people learning Chinese in Indonesia has also increased significantly. That way the demand for Chinese teachers in Indonesia is in-creasing slowly . In 2004, Hanban launched the "Chinese Teacher Volunteer" project in which thousands teachers are sent to various countries around the world every year to teach Chinese and spread Chinese culture. Most of the volunteer Chinese teachers have been working and living abroad for a long time, and in this long-term foreign cultural atmosphere, they have more contact with the locals, not only from theoretical understanding, but also from practical life, they will continue to face difficulties, especially in terms of cultural ad-aptation, they will experience a kind of culture shock, which will be reflected in these Chinese teachers. The authors randomly selected a Chinese teacher teaching mandarin in Indonesia to conduct an interview survey to investigate how they reflect differently in cross-cultural communication under the collision of different cultures in China and Indonesia. After consolidating interviewees, the authors found that the explicit culture of interviewees in foreign countries includes: language, food, etiquette, systems, and clothing; Implicit ones in-clude: religion, the concept of time, etc. It is hoped that this survey can provide assistance, references and advice to teachers who will volunteer as Chinese teachers in Indonesia in the future, making it more convenient for teachers to work, study, and live in Indonesia.